Ant-Based Contention-Resolution Schemes for Shared Fiber-Delay Line Optical Packet Switches - Chin, Tan Saw; Abbou, F. M.; Tat, Ewe Hong (INFOCOMP Journal of Computer Science, 2007)
This paper studies the Ant-based packet contention resolution schemes for the singlestage shared FDL optical packet switches. A new Ant-based algorithm is proposed, namely delaybased FDL assignment and number–delay-based FDL assignment. The proposed algorithm can makes FDLs and output port reservation so as to improve the cell-loss rate under various traffic loads. The proposed contention resolution scheme is shown to effectively resolve packet contention and achieve good performance by requiring minimum fiber delay length.